Relationship between Soil Property and the Aggregation of Tropical Forest Soils in Thailand - Suwanprapa, Wanrapee; Anusontpornperm, Somchai; Thanachit , Suphicha; Kheoruenromne , Irb (Agriculture and Natural Resources, 2015)
The aggregate size distribution and its relationships with other soil properties were determined in eight soils under different tropical forest types: secondary mixed deciduous forest, dry dipterocarp forest, dry evergreen forest and an ecotone zone. The aggregate stability of individual aggregate size fractions WSA1 to WSA6 were determined by a wet-sieving method as: 2 mm ≤ WSA1 <8 mm; 1 mm ≤ WSA2 < 2 mm; 0.5 mm ≤ WSA3 < 1 mm; 0.25 mm ≤ WSA4 < 0.5 mm ; 0.1 mm ≤ WSA5 < 0.25 mm; and WSA6 < 0.10 mm.. They were moderately shallow to very deep and slightly to strongly acidic. The soil texture was sandy loam to clay with low to high levels of organic matter content (2.0–18.7 g.kg-1), available phosphorus (0.13–0.17 mg.kg-1), available potassium (11–174 mg.kg-1), and cation exchange capacity (4.5–38.5 cmolc.kg-1). There were no differences in the aggregate size distribution among the soils with nearly half of the net aggregates being dominated by macroaggregate size WSA1, especially in the topsoil layers. Organic carbon, available P, bulk density, sand+silt and the clay fractions, and extractable Mg, Fe and Mn played important roles in the water stability of aggregation of these soils in different sizes. Organic carbon was the main source contributing to the formation of macroaggregates (r = 0.77in the topsoils, which consequently reduced the bulk density of these soils (r= -0.58 ). Various amorphous forms of Fe, especially in the amorphous form, were clearly involved in the formation of microaggregates (below 2.5 mm) in subsurface soils.